The creative Kingdom: economic reform and art as a new space of Islamic critique in Saudi Arabia - Cubelic, Danijel (Zeitschrift für Religionswissenschaft, 2019)
Whilst the field of contemporary art has been impeded until recently by Saudi Arabia's blasphemy laws and heavy censorship, the last decade has seen a rapid growth of art networks and institutions. Incidents such as the conviction of internationally lauded artist and curator Ashraf Fayadh in 2015 on charges of apostasy show that Islamic authorities still claim to define what is acceptable and not acceptable in the field of cultural production, but several renowned Saudi artists have started to question the hegemony of the Islamic field. This article discusses these processes in the context of radical economic reform led by the Saudi crown prince Mohammed bin Salman. Why do state actors see an investment in art and creativity as a necessity for economic renewal? What role does contemporary art play in strategies to rebrand the negative image of Saudi Arabia? How do artists relate to Islamic narratives and material culture to claim authority in Islamic debates and provide legitimacy for their concerns? By focusing on the interactions between economic reform and new spaces of Islamic critique, the paper aims to shed light on the way in which the drive for economic transformation is remapping the social boundaries between Islamic authorities, the creative economy and the state.
Veröffentlicht: 9. April 2019
Keywords: Kritik; Islam; Kunst; Wirtschaftsreform; Saudi-Arabien